2021
DOI: 10.1021/acs.jpcc.1c05724
|View full text |Cite
|
Sign up to set email alerts
|

Nonaqueous Solvent Adsorption on Transition Metal Surfaces with Density Functional Theory: Interaction of N,N-Dimethylformamide (DMF), Tetrahydrofuran (THF), and Dimethyl Sulfoxide (DMSO) with Ag, Cu, Pt, Rh, and Re Surfaces

Abstract: Interfaces between solvents and transition metals play a critical role in many catalytic and electrochemical systems. In this work, we use density functional theory (DFT) to study the interactions between several common nonaqueous solvents and a number of transition metal surfaces. We investigate trends in binding energies among the metals, and the influence of specific surface sites and facets. We examine the electrostatic field dependence of the most stable binding configurations, and shed light on experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 150 publications
0
8
0
Order By: Relevance
“…Similar qualitative trends in CO 2 RR were also reported by Berto et al and Shi et al, where voltammetric experiments in the presence of NBu 4 + electrolytes have shown larger current density values for CO 2 RR in highly polar DMF and MeCN, as compared to low polarity THF. Here, DMSO has the largest standard deviation (Figure ), which was also found to exhibit the largest deviation from trends due to coordination via the sulfur atom (as opposed to via the oxygen atom in water and THF) in a study of aprotic solvent (THF, DMF, and DMSO) adsorption on metal surfaces by Nørskov and co-workers . In aprotic solvents and NBu 4 + salts, tailoring the lifetime of the CO 2 – will likely depend on solvent, due to the stabilizing influence of more polar solvents.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Similar qualitative trends in CO 2 RR were also reported by Berto et al and Shi et al, where voltammetric experiments in the presence of NBu 4 + electrolytes have shown larger current density values for CO 2 RR in highly polar DMF and MeCN, as compared to low polarity THF. Here, DMSO has the largest standard deviation (Figure ), which was also found to exhibit the largest deviation from trends due to coordination via the sulfur atom (as opposed to via the oxygen atom in water and THF) in a study of aprotic solvent (THF, DMF, and DMSO) adsorption on metal surfaces by Nørskov and co-workers . In aprotic solvents and NBu 4 + salts, tailoring the lifetime of the CO 2 – will likely depend on solvent, due to the stabilizing influence of more polar solvents.…”
Section: Resultsmentioning
confidence: 78%
“…Here, DMSO has the largest standard deviation ( Figure 3 ), which was also found to exhibit the largest deviation from trends due to coordination via the sulfur atom (as opposed to via the oxygen atom in water and THF) in a study of aprotic solvent (THF, DMF, and DMSO) adsorption on metal surfaces by Nørskov and co-workers. 61 In aprotic solvents and NBu 4 + salts, tailoring the lifetime of the CO 2 – will likely depend on solvent, due to the stabilizing influence of more polar solvents.…”
Section: Resultsmentioning
confidence: 99%
“…However, the synthesis suffers from some limitations. DMF can interact relatively strongly with metal surfaces . DMF itself is a relatively non-ecofriendly solvent with a high boiling point.…”
Section: Colloidal Surfactant-free Synthesesmentioning
confidence: 99%
“…e electrondonor capability of the aprotic solvent also determines the adsorption of organic molecules on the cathode surface [55][56][57]. Reactions ( 13) and ( 15) take place on the latter, the course of which depends on the adsorption-desorption of CO 2 and CO molecules, CO 2 radicals, and CO 3 (2) Influence of CO 2 Solubility.…”
Section: Influence Of Thementioning
confidence: 99%